ATICC: a mixed-methods study on addiction, trauma, and immigration among vulnerable young adults in the grand est youth network - Maha Najdini; Antoine Frigaux; Joris Mathieu; Gérard Shadili; Tamara Guenoun; Xanthie Vlachopoulou; Rose-Angélique Belot; Ariane Bazan; Florence Gressier; Marion Robin; Aziz Essadek (BMC Psychology)
Abstract Background This research protocol for the study ATICC (Addiction, Trauma and Immigration, prevention and Cross-Cultural support for care with the Grand Est youth network) aims to model the complex interrelations between trauma, substance use behaviors, migration and representations of mental health among vulnerable youth residing in Transitional Housing for Young Adults. This study focuses on a specific and underexplored population, many of whom have experienced traumatic events and/or complex migratory trajectories. The ultimate objective of this research is to develop transferable models of understanding that can inform the design of prevention and support programs tailored to this demographic. Methods/Design We adopt a tripartite methodology approach: (1) a cross-sectional study using standardized questionnaires to identify factors associated with substance use, trauma, and barriers to healthcare access; (2) an in-depth qualitative study based on semi-structured individual interviews with substance users, exploring their subjective experiences and perceptions related to substance use and mental health care; and (3) a longitudinal interventional study involving various configurations of focus groups open to residents of transitional housing structures, aiming to assess the impact of these group sessions on participants’ psychological well-being and attitudes toward care. Quantitative analyses will include descriptive and multivariate statistical tests using R, while qualitative data will be analyzed through thematic analysis with NVivo. The effectiveness of the group intervention will be evaluated using pre/post-tests, mixed models, and appropriate statistical corrections. Discussion Analyses are expected to identify key psychosocial factors influencing addictive behaviors and mental health, highlight cultural and structural barriers to care, and assess the psychological benefits of the group intervention. The ATICC study aims to contribute to the development of culturally adapted prevention and support models for young adults in precarious situations. The results should assist healthcare professionals and policymakers in designing evidence-based interventions that effectively address the specific needs of this population. Trial registration This study is registered with the Biomedical Research Identification Number (n°ID-RCB) assigned in France by the National Agency for the Safety of Medicines and Health Products (ANSM): 2024-A01534-43, and have received the approval from the committee for the protection of persons (CPP) Ile-de-France on November 18, 2024. Cette étude a également été déposée sur clinicaltrials (NCT06922721, date assigned April 10, 2025).